ASUHAN KEPERAWATAN PADA PASIEN ULKUS DEKUBITUS DENGAN MASALAH UTAMA GANGGUAN INTEGRITAS JARINGAN DI RS NISHIHARA KEIAIEN JEPANG - ANANDA, YORDAN DISKA; Eko Kurniawan, Wasis; Sumarni, Tri (STIKES dan AKZI Karya Husada Kediri, 2025)
Pressure sores or decubitus ulcers are conditions with injury to the skin or soft tissue located over a protruding bone, or caused by medical devices or other equipment. This study aims to describe appropriate nursing care and interventions for decubitus ulcer patients with impaired tissue integrity. The research method used is descriptive with a case study approach.. The case study instruments used were nursing care documentation format, observation, interviews, and physical examinations. A Case Study showed that after nursing intervention was carried out for 3 days. Skin/tissue integrity problems were partially resolved, with the criteria: decrease of tissue damage, improved skin layer damage, decreased redness, and pain. Treatment of pressure ulcers and bed sores must be carried out routinely and accompanied by pharmacological therapy so that patients can recover optimally